Binding conformers searching method for ligands according to the structures of their receptors and its application to thrombin inhibitors - Jiang Hua-Liang; Chen Kai-Xian; Tang Yun; Chen Jian-Zhong; Li Quan; Wang Qin-Mi; Ji Ru-Yun (Acta Pharmacologica Sinica, 2016)
AIM: To develop a method of finding binding conformers for ligands according to the three-dimensional structures of their receptors. METHODS: Combining the systematic search method of ligand with the molecular docking approach of ligand fitting into its receptor, we developed a binding conformer searching method for ligands. RESULTS: The binding conformers of phosphonopeptidyl thrombin inhibitors were recognized. The binding (interaction) energies between these inhibitors and thrombin were calculated with molecular mechanical method. CONCLUSION: Both of the total binding energies and steric binding energies have good correlations with the inhibitory activities of these thrombin inhibitors, demonstrating that our approach is reasonable. It can also be used to explain the inhibition mechanism of thrombin interacting with these inhibitors.